Paul Maenz Köln 1970 - 1980 - 1990 : Eine Avantgarde-Galerie und die Kunst unserer Zeit : Lebendige Geschichte - Kuspit, Donald; Faust, Wolfgang Max; Maenz, Paul; Paul Maenz, Köln (Köln : DuMont Buchverlag, 1991)
Art & Language ; Barry, Robert ; Bömmels, Peter ; Clemente, Francesco ; Cucchi, Enzo ; Dahn, Walter ; Dokoupil, Georg ; Disler, Martin ; Haacke, Hans ; Haring, Keith ; Kiefer, Anselm ; Kosuth, Joseph ; Maloney, Martin ; Paladino, Mimmo ; Penone, Giuseppe ; Roehr, Peter ; Salvo ; Scholte, Rob ; Sturtevant ; etc.
boek